2012
DOI: 10.1002/anie.201203360
|View full text |Cite
|
Sign up to set email alerts
|

A Phenylboronate‐Functionalized Polyion Complex Micelle for ATP‐Triggered Release of siRNA

Abstract: Therapeutics based on small interfering RNA (siRNA) offer an attractive clinical option because of its ability to silence genes in a highly sequence-specific manner.[1] A key challenge lies in developing a delivery system that helps protect the siRNAs from endogenous RNase degradation while allowing for controlled pharmacokinetics. One promising approach is a formulation of polyion complex (PIC) micelles that spontaneously form in an aqueous environment simply through electrostatic interactions between the ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
159
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 213 publications
(160 citation statements)
references
References 26 publications
1
159
0
Order By: Relevance
“…Similar to the aforementioned environment-responsive delivery vehicles, delivery vehicles can be designed to release payload siRNA into the ATP-abundant cytosol by utilizing phenylboronic acid (PBA) chemistry. PBA can form reversible covalent esters with 1,2-cis-diols on a ribose ring, which is present at the 3´end of siRNA and ATP [139]. As a representative, 3-fluoro-4-carboxyphenylboronic acid (FPBA) was conjugated into primary amino groups in the side chain in PEG-polycations and complexed with the ribose-terminated siRNA as an intermolecular crosslinker [ Fig.…”
Section: Atp Concentration-responsive Delivery Vehiclesmentioning
confidence: 99%
“…Similar to the aforementioned environment-responsive delivery vehicles, delivery vehicles can be designed to release payload siRNA into the ATP-abundant cytosol by utilizing phenylboronic acid (PBA) chemistry. PBA can form reversible covalent esters with 1,2-cis-diols on a ribose ring, which is present at the 3´end of siRNA and ATP [139]. As a representative, 3-fluoro-4-carboxyphenylboronic acid (FPBA) was conjugated into primary amino groups in the side chain in PEG-polycations and complexed with the ribose-terminated siRNA as an intermolecular crosslinker [ Fig.…”
Section: Atp Concentration-responsive Delivery Vehiclesmentioning
confidence: 99%
“…[32][33][34] In addition, PBA is capable of forming reversible covalent esters with the ribose ring of DNA or siRNA, thus cationic polymers modifi ed with PBA can bind with nucleic acid via the boronic ester linkage except ionic interactions. [ 35 ] PBA containing polymers are also used as gene vectors based on these promising properties. [36][37][38] Furthermore, PBA has a…”
mentioning
confidence: 99%
“…4). 56 PBA is able to reversibly bind with ribose, the binding constant of which is quite high relative to those for other common sugars. We found that the binding between the pendent PBA and 3′end ribose at both ends of double stranded siRNA along with hydrophobic interaction contribute to stability of the complex in quasi-extracellular conditions.…”
Section: ·1 Sirna Deliverymentioning
confidence: 96%